Lack of association of NAT2 (N-acetyl transferase 2) gene polymorphism with atopic asthma in Turkish subjects - (:unkn) unknown (My University, 2004)
It has been shown that slow acetylation may be a risk factor that influences the development of allergic diseases. N-acetyltransferase2 (NAT2), an enzyme that degrades autocoids and drugs, shows a bimodal distribution of rapid and slow acetylators with broad interethnic variation. This case-control study was designed to investigate the association of genotypes that encode slow and rapid activity of NAT2 with asthma and asthma severity in the Turkish population. Turkish unrelated atopic subjects with asthma (n=57) and unrelated healthy subjects (n=56) were enrolled in this case-control study. The locus coding for NAT2 was genotyped by means of the polymerase chain reaction. Multivariate logistic regression models were constructed to investigate the relationship between NAT2 genotypes and case-control status.The frequency of slow acetylators inferred from NAT2 genotype was not significantly different in asthmatic subjects (47%) and healthy subjects (43%) (P<0.55). No significant association was found between NAT2 genotype and either disease severity or duration within the case group (P<0.19 and P<0.17, respectively). This study suggests that the NAT2 (slow acetylation) genotype is not a marker of predisposition for atopic asthma and severity of asthma in the Turkish population.
Keywords: Asthma; Genetics; NAT2 (N-acetyl transferase2); Turkey